1996
DOI: 10.1080/17450399609381894
|View full text |Cite
|
Sign up to set email alerts
|

Effect of feeding various dietary vitamin B6concentrations during gestation and lactation on vitamin B6level in liver and carcass of rat dams

Abstract: The present investigation was designed to determine the vitamin B6 concentration in liver and carcass of rat dams fed various dietary vitamin B6 levels during gestation and lactation. Therefore, gravid female rats received 0.6, 3, 6, 18 or 180 mg vitamin B6 per kg diet. After parturition each group was divided into 2 groups of 8 dams each, which received then a diet with 3, respectively 6 mg/kg vitamin B6 during lactation. At the end of the experiment at day 14 of lactation weight gain and food consumption as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1997
1997
1998
1998

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…For thiamin, it has been demonstrated that a high supply during pregnancy increases thiamin storage in the body, and therefore the thiamin supply during pregnancy markedly influences both the thiamin status during lactation and the thiamin concentrations in the milk (R oth ‐M aier et al 1990; K irchgessner et al 1997). In contrast, for vitamin B 6 it has been shown that a high supply during pregnancy does not produce additional storage (R eithmayer et al 1985), and therefore vitamin B 6 supply during pregnancy only had a slight influence on the vitamin B 6 status during lactation (R oth ‐M aier et al 1996; B enedikt et al 1996). In order to investigate the physiological behaviour of riboflavin in this respect, rats were fed diets with various supplementary levels of riboflavin during pregnancy and lactation and the concentrations of riboflavin were determined in the liver and carcass after pregnancy and lactation and in the milk of lactating rats.…”
Section: Introductionmentioning
confidence: 99%
“…For thiamin, it has been demonstrated that a high supply during pregnancy increases thiamin storage in the body, and therefore the thiamin supply during pregnancy markedly influences both the thiamin status during lactation and the thiamin concentrations in the milk (R oth ‐M aier et al 1990; K irchgessner et al 1997). In contrast, for vitamin B 6 it has been shown that a high supply during pregnancy does not produce additional storage (R eithmayer et al 1985), and therefore vitamin B 6 supply during pregnancy only had a slight influence on the vitamin B 6 status during lactation (R oth ‐M aier et al 1996; B enedikt et al 1996). In order to investigate the physiological behaviour of riboflavin in this respect, rats were fed diets with various supplementary levels of riboflavin during pregnancy and lactation and the concentrations of riboflavin were determined in the liver and carcass after pregnancy and lactation and in the milk of lactating rats.…”
Section: Introductionmentioning
confidence: 99%